Titanium - ceramic restoration: How to improve the binding between titanium and ceramic - Harry Laksono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Titanium alloys has been used as an alternative to nickel-chromium alloys for metal-ceramic restorations because of its good biocompatibility and mechanical properties. This indicated that it was possible to design coping according to standards established for metal-ceramics. However, titanium is chemically reacting strongly with gaseous elements which causes problems when ceramics are fused to titanium. Purpose: To provide information about improving the bonding between titanium and ceramic. Review: Titanium has two crystal modifications, the close-packed hexagonal (α) structure, up to 880° C, and above this temperature the bodycentered cubic (β) structure. The principal problems is the extensive dissolution of oxygen resulting in thick, oxygen-rich titanium layers called α-case that harms the bonding of ceramic to titanium and the great mismatch in the coefficient of thermal expansion of conventional ultra-low fusing ceramic. Methods have been developed for fusing ceramic to titanium like processing methods, the used of ultra-low fusing titanium ceramic, bonding agent, and protocol for ceramic bonding to titanium. Conclusion: Titanium and titanium alloys, based on their physical and chemical properties suitable for titanium-ceramic restorations, but careful selection of processing methods, ceramic materials, laboratory skill and strict protocol for ceramic bonding to titanium are necessary to improve the bonding between titanium and ceramic.Latar Belakang: Logam campur titanium telah dipakai sebagai salah satu bahan alternatif untuk logam nikel-krom pada pembuatan restorasi keramik taut logam karena mempunyai biokompatibilitas dan sifat mekanik yang baik. Hal ini menunjukkan bahwa logam titanium dapat dipakai untuk pembuatan koping logam berdasarkan standar yang dipakai untuk pembuatan restorasi keramik taut logam. Meskipun, secara kimiawi logam titanium bereaksi dengan elemen-elemen gas yang menyebabkan masalah pada perlekatan keramik pada titanium. Tujuan: Memberikan informasi tentang cara meningkatkan kekuatan perlekatan antara keramik dengan titanium. Tinjauan: Titanium mempunyai 2 struktur kristal, struktur close-packed hexagonal (α) diatas 880°C dan struktur bodycentered cubic (β) dibawah 883°C. Masalah utama adalah pelepasan gas oksigen yang menghasilkan lapisan titanium kaya oksigen yang tebal disebut α-case yang menghalangi perlekatan keramik pada titanium dan koefisien ekspansi panas dari bahan ultra-low fusing ceramic yang berbeda dengan titanium. Berbagai cara telah dikembangkan untuk mendapatkan perlekatan keramik pada titanium seperti teknik pembuatan, pemakaian bahan ultra-low fusing titanium ceramic, bahan bonding dan protokol untuk perlekatan bahan keramik pada titanium. Kesimpulan: Titanium dan logam campur titanium, berdasarkan sifat-sifat mekanik dan kimiawinya dapat dipakai untuk pembuatan restorasi keramik taut logam, tetapi pemilihan teknik pembuatan, bahan keramik, ketrampilan peteknik gigi dan mengikuti protokol untuk mendapatkan perlekatan keramik pada titanium dengan benar diperlukan untuk meningkatkan kekuatan perlekatan antara keramik dan titanium.